Self-reported and clinically determined oral health status predictors for quality of life in dentate older migrant adults - MarinËœo R, Schofield M, Wright C, Calache H, Minichiello V. (Blackwell Synergy, 2008)
This paper reports the impact of oral health on the quality of life (QOL) of Southern European, dentate older adults, living independently in Melbourne, Australia